Factor market disequilibrium in neoclassical and neo-Keynsian models - Neary, J; Neary, Peter (1978)
This thesis explores two different approaches to the study of simple general equilibrium models in situations where "full" or "long-run" equilibrium does not prevail. The first part of the thesis examines the consequences of dynamizing the two-sector model of competitive equilibrium, in the sense of making explicit the process whereby momentary equilibrium (i.e., full equilibrium with a given factor endowment) is attained. A number of plausible adjustment mechanisms are proposed, of which the "short-run capital specificity" hypothesis is an interesting special case. The implications of these adjustment mechanisms for international trade theory, for the theory of proportional factor market distortions in both open and closed economies, for the behaviour of the Harris-Todaro model when capital is intersectorally mobile, and for the dynamic response of the trade balance to a devaluation in a small open economy are then examined. The second part of the thesis studies the properties of a neo-Keynesian temporary equilibrium, by which is meant a shortperiod equilibrium where agents base their behaviour on their expectations about the future and where prices and wages do not move to clear markets in the short run. It is shown that the closed economy model of Malinvaud and the open economy model of Dixit are both special cases of a more general model which incorporates a non-traded good whose price is sticky in the short run, and a traded good, whose price is determined on world markets. While the long-run properties of this model are shown to be fully consistent with the monetary approach to the balance of payments (so, for example, a devaluation has no real long-run effects), its short-run comparative statics properties are shown to provide, in some circumstances, considerable support for discretionary policy.